“We are doing the best we can to bridge the gap” - service provider perspectives of educational services for autism spectrum disorder in South Africa - Pillay, Sarosha; Duncan, Madeleine; de Vries, Petrus J. (Frontiers in Psychiatry, 2022)
Background The South African education system is increasingly unable to meet the growing needs of children with autism spectrum disorder (ASD). Recent studies in the Western Cape, one of the better resourced provinces in South Africa, showed that the pathway to care for children with ASD was an inconsistent and lengthy process, and that many children with ASD waited for extended periods to get access to an appropriate school placement. It is therefore clear that scalable and sustainable solutions are required to improve access to appropriate education for children with ASD. Methods Here we performed a qualitative study using thematic analysis of ten multi-sectorial ASD service provider interviews in the Western Cape Province to examine provider perspectives and proposed solutions to meet the educational needs of children with ASD. Results Provider perspectives were grouped in three categories: “bridging the gap across the spectrum and lifespan”, “gaps to bridge”, and “building bridges”. The first category captured provider perspectives of the service-related needs inherent to a diagnosis of ASD. The second category summarized service provider views of the challenges associated with providing services to children with ASD and the third category captured provider perspectives on potential actions to improve ASD education services delivery in the province. The overarching theme that emerged was “We're doing the best we can to bridge the gap”. Conclusion Participants provided ten key recommendations for service strengthening that may lead to contextually relevant innovations to meet the educational needs of children with ASD in the province. Findings from this study has direct relevance to other South African provinces and may have relevance to improve pathways and reduce service delivery gaps also in other low-and-middle-income countries.